Alimenter la ville de Lyon en eau : les galeries de captage antiques sous les collines de Fourvière et de la Croix-Rousse - Emmanuel Bernot (Gallia)
The hills of Lyon contain large natural water reserves in their subsoil which helped to supply the parts of Lyon located on the slopes of the hills, on the right bank of the Saône and on the peninsula from Antiquity through to the 19th century.Following the landslide that occurred in 1930 on the eastern slope of the Fourvière hill, the city undertook major drainage and reinforcement work in these ancient networks of underground galleries. For more than ten years, the City of Lyon’s Archaeological Department, in partnership with the Metropolitan Council’s services, has been regularly monitoring these reinforcement operations. This research has enabled us to identify several Roman water collection galleries, providing us with new insight into the water supply to the ancient city of Lyon/Lugdunum.The principle of these galleries is simple. It consists either in channelling water from springs emerging from the hillsides, or in digging a gallery, sometimes leading from the bottom of a well, to capture infiltration water in the top of a clay layer. These galleries could be left in the ground, without any particular reinforcement, and the water would be captured by capillary action through the substrate. Some of them might be lined. The bottom might be formed by the substrate itself, especially if it is rocky, or covered with boards, tiles or bricks to facilitate water flow. It could also be fitted with an open or covered gutter. These different arrangements are found without distinction in all periods. Most of the sedimentary formations forming the Fourvière and Croix-Rousse hills are conducive to water circulation and the aquifer levels are therefore concentrated in contact with impermeable or low-permeability formations, such as basalt and clay. The Croix-Rousse hill, which rises to an altitude of about 250 m NGF, has particularly abundant aquifer resources spread over a height of about 60 m. The upper part of the Fourvière hill, on the other hand, is mostly devoid of natural water resources and the majority of the wells that have been identified there to date are located between 210 and 230 m NGF above sea level, although some have been found at higher altitudes.A first network of Roman galleries was identified on the slopes of the Fourvière hill, at the bottom of the Rosaire garden. It consists of a straight masonry section with a branch to the west, though only a few dozen centimetres of this was preserved before it collapsed. A second section, laid out in the open ground, extends from the first section and the water flows inside a brick-covered channel. The start of another gallery, also in open ground, was observed from this last section: this time its base is formed of a plank-lined wooden invert. The construction of this network may date from the 1st century AD. Several Roman water supply pipes fed by natural springs have been identified at the foot of the hillsides, on the right and left banks of the Saône. On the northern slope of the Fourvière hill, a spring catchment was recently discovered on the Montée de l’Observance. It takes the form of a small masonry gallery with a niche constructed on its base to collect water.Under the southern slope of the Croix-Rousse hill, to the north of the peninsula, three open-ground Roman water galleries have been uncovered in recent years. Two of them were carbon dated to between the 1st and 3rd centuries AD. The third can be reconstructed over a length of 120 m and has a masonry gutter at its base covered by a protective layer of rubble. It runs roughly in a straight line, apart from a chicane-shaped drop in its central part corresponding to a connecting bend and testifying to its excavation from both ends. Its southern wall is punctuated with regularly spaced cubicles designed to hold oil lamps. Finally, five small diameter wells were observed at the top of its vault, near the surface, allowing us to link this structure to qanat-type galleries.From flow measurements taken in certain gallery networks and the assessment of the hydraulic potential of the hills, the contribution of these galleries and natural springs can be estimated at several thousand cubic metres per day. However, in Lyon, each gallery could probably only provide a small flow, as it collected water through the substrate by capillary action. Their contribution to a more extensive supply network therefore necessarily implied their convergence towards reservoirs in order to put the water under pressure.The water collection galleries under the hills, exploited at least since the 1st century AD, as well as the channelled springs, were therefore used –either directly or in addition to other sources– to supply public or private hydraulic infrastructures located on the slopes or at the foot of the hills: thermal baths, basins, cisterns, wells and fountains. On the Fourvière hill, these springs and galleries would have supplemented the water supplied by the aqueducts, which were essential for the supply of the upper town, for which there were no easily accessible natural water resources. On the peninsula and on the slopes of the Croix-Rousse hill, their contribution to the water supply was undoubtedly even more important and could explain the absence of a Roman aqueduct in this part of the ancient city.